2021
DOI: 10.3390/polym13162583
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Curcumin in Crosslinked Jelly Fig Pectin Using Vacuum Spray Drying Technique for Effective Drug Delivery

Abstract: Microencapsulation of curcumin in jelly fig pectin was performed by the vacuum spray drying (VSD) technique. The VSD was advanced with a low inlet temperature of 80–90 °C and low pressure of 0.01 mPa. By the in situ cross-linking with multivalent calcium ions, jelly fig pectin produced stable curcumin encapsulated microparticles. The physiochemical characteristics of microparticles were thoroughly investigated. The results revealed that 0.75 w/w% of jelly fig pectin and inlet temperature of 90 °C could be feas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
5
8
1
Order By: Relevance
“…In contrast, Tsai, et al [ 40 ] reported the slow release of curcumin nanoparticles loaded in poly(lactic-co-glycolic acid) with biphasic releasing pattern and 59% release occurred after 12 h, which further increased up to 89% at the end of 6 days. The findings further in lined with the earlier study, in which microencapsulated curcumin in crosslinked jelly fig pectin exhibited a cumulative release of 95.34% over 24 h [ 41 ]. Similarly, Reddy, et al [ 23 ] observed the high release of curcumin (45 to 65%) encapsulated in mixture of sodium alginate/montmorillonite into the dissolution medium at pH 7.40.…”
Section: Resultssupporting
confidence: 90%
“…In contrast, Tsai, et al [ 40 ] reported the slow release of curcumin nanoparticles loaded in poly(lactic-co-glycolic acid) with biphasic releasing pattern and 59% release occurred after 12 h, which further increased up to 89% at the end of 6 days. The findings further in lined with the earlier study, in which microencapsulated curcumin in crosslinked jelly fig pectin exhibited a cumulative release of 95.34% over 24 h [ 41 ]. Similarly, Reddy, et al [ 23 ] observed the high release of curcumin (45 to 65%) encapsulated in mixture of sodium alginate/montmorillonite into the dissolution medium at pH 7.40.…”
Section: Resultssupporting
confidence: 90%
“…Secondly, the PdI represents the distribution of uniform particles in the sample, the lower the PdI value, the more uniform the particle size (Strobel et al, 2016). The emulsion prepared with gum arabic/high methoxyl pectin exhibited a low viscosity value of 120 cP, which agrees with that reported by Hartini et al (2021), for an emulsion prepared with jelly fig pectin with a viscosity range from 17 to 186 cP. This low viscosity could generally produce small size droplets during spray drying, however, the PdI of 0.58 suggests the presence of a heterogenous distribution of particle size in emulsion and after spray drying.…”
Section: Characterization Of Bacterial Emulsionsupporting
confidence: 87%
“…This effect can be explained by the strong repulsive forces between the formed droplets, mainly due to the combination of electrostatic and steric forces derived from the proteinaceous content of gum arabic positively charged and high methoxyl pectin & Wicker, 2021). The gelation capacity of pectin first generates an increase in emulsion viscosity and later a larger size in the droplets obtained from the stirring (Hartini et al, 2021). Furthermore, esterified groups of high methoxyl pectin can interact with the H-1 and H-2 groups of glucoronic acid units of alginate, generating layers on the surface of alginate capsules leading to lower porosity, larger particle size and a decreased in surface-volume ratio resulting in less diffusion of the active center, the latter derived from the formation of membranes with high resistance to rupture and coalescence (Esfanjani et al, 2017;Arab et al, 2019).…”
Section: Characterization Of Bacterial Emulsionmentioning
confidence: 99%
See 2 more Smart Citations